On the legislation of the Republic of Kazakhstan in the field of protection against unfair competition. (Journal of actual problems of jurisprudence, 2016)
The article discusses the legal regulation of unfair competition, to protect businesses and consumers from monopolistic activities and actions of state bodies and unfair competition. Along with that analyzed the basic concepts of unfair competition , as the spread distorted information capable of causing losses to the economic entity, the consumer, misleading, incorrect comparison of the subject goods produced by them with the products of other subjects , the disclosure of information constitutes a trade secret.
Keywords: unfair competition; business entity; an administrative offense; the sanction